The power of "varas": the councils in Piura at the end of the colony - Diez Hurtado, Alejandro (1992)
This article examines the organization and the functioning of the indian councils in Piura highlands, during the late colonial period. It aims to show that the indian and peasant community of today is a product of the colonial period. The councils of the past were used institutionally by the Spanish to impose a system of government based on family differentiation with the indian communities. The councils were institutionalized, established their own expressions of power, classified social groups, and became the vehicles for community protest; a peasant leadership evolves within them, resembling the previous 'cacique' (local chieftain) administrations.